Intravenous immunoglobulin as an important adjunct in the prevention and therapy of coronavirus 2019 disease. (16th September 2021) - Danieli, Maria Giovanna; Piga, Mario Andrea; Paladini, Alberto; Longhi, Eleonora; Mezzanotte, Cristina; Moroncini, Gianluca; Shoenfeld, Yehuda
Abstract: The coronavirus disease‐19 (COVID‐19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) challenged globally with its morbidity and mortality. A small percentage of affected patients (20%) progress into the second stage of the disease clinically presenting with severe or fatal involvement of lung, heart and vascular system, all contributing to multiple‐organ failure. The so‐called 'cytokines storm' is considered the pathogenic basis of severe disease and it is a target for treatment with corticosteroids, immunotherapies and intravenous immunoglobulin (IVIg). We provide an overview of the role of IVIg in the therapy of adult patients with COVID‐19 disease. After discussing the possible underlying mechanisms of IVIg immunomodulation in COVID‐19 disease, we review the studies in which IVIg was employed. Considering the latest evidence that show a link between new coronavirus and autoimmunity, we also discuss the use of IVIg in COVID‐19 and anti‐SARS‐CoV‐2 vaccination related autoimmune diseases and the post‐COVID‐19 syndrome. The benefit of high‐dose IVIg is evident in almost all studies with a rapid response, a reduction in mortality and improved pulmonary function in critically ill COVID‐19 patients. It seems that an early administration of IVIg is crucial for a successful outcome. Studies' limitations are represented by the small number of patients, the lack of control groups in some and the heterogeneity of included patients. IVIg treatment can reduce the stay in ICU and the demand for mechanical ventilation, thus contributing to attenuate the burden of the disease.